Answer:
y = 3
x = -1
Step-by-step explanation:
The idea to start the problem is that we need to cancel x in one equation to find y first, therefore:
y = -x + 2 (let's multiply this entire equation by -4)
y = -4x - 1
We then have .:
- 4y = 4x - 8
y = -4x - 1 (now we sum both equations)
.:
- 3y = -9 (isolate y)
y = -9 / -3
y = 3 (good we have y!)
Now come back to one of the equations, substitute y to find your x!
Substituting on the first equation we have:
3 = -x +2 (isolate x)
3 - 2 = -x
1 = -x (multiply everything by -1)
x = -1
I hope it helps :)